Ta’līm Al-Lughah Al-’Arabiyyah baina Al-Ṭarīqah Al-Sam’iyyah Al-Syafawiyyah wa Dūnihā li Ṭullāb Al-Ṣaf Al-Ṡāmin bi Al-Madrasah Al-Ṡānawiyyah Al-Islāmiyyah Al-Ma’ārif 1 Ponorogo - Amir Mukminin (Study Program of Arabic Language Teaching, 2020)
This research was taken to find out the effectiveness of with and without the audio-lingual method in teaching Arabic for students of the eighth grade of the Islamic Secondary School Ma’arif 1 Ponorogo. This experimental research is quantitative. The samples were 20 students. In collecting data, a documentary interview was used. The results of the research are: (1) The result of teaching Arabic with the audio-lingual method for students of the eighth grade of the Islamic high school Ma’arif 1 Ponorogo was Very Good with a score of 90,625%; (2) The result of teaching Arabic without the audio-lingual method for students in the eighth grade of the Islamic High School Ma’arif 1 Ponorogo was Good with a score of 75,52%; (3) A meaningful comparison between the results of teaching Arabic with and without the audio-lingual method to students of the eighth grade of the Islamic Secondary School Ma’arif 1 Ponorogo was found. It is because t-score (2,02) > t-table (2,742) has a meaningful score of 5%.